Factors of Confidence of Online Shoppers that Affect Buyer's Satisfaction in Bangkok - Phumphongkhochasorn, Phumphakhawat; Nanposri, Natamon (Rajapark Journal, 2022)
The objectives of this research were to 1) study the level of confidence of online shoppers that affects the satisfaction of shoppers in Bangkok; 2) compare the confidence of shoppers and the preferences of shoppers; and 3) present the influences between the behavior of shoppers online. This was quantitative research. The research tool was a questionnaire to collect data from a sample of online shopping that affects the satisfaction of shoppers between 20-50 years old in Bangkok. It consisted of 400 people, and the statistics used in the research were frequency, percentage mean, standard deviation, F-test, and multiple regression analysis. The study's findings revealed that: 1) the level of confidence of online shoppers influenced Bangkok shoppers' satisfaction. It was at a very good level. 2) Comparison of the confidence of the purchasers and the satisfaction of the purchasers. There was a statistically significant level at .05 and 3) the influence between the behavior of shoppers online. and customer satisfaction in terms of environmental and social service systems, personal and psychological forecast the influence between online shoppers’ behavior and shoppers' preferences with a value of R2=.279.